Microhemodynamic Parameters of Cortical Substance of Kidneys at Experimental Hydronephrosis - Bakhtiyar Iriskulov1, Ra’no Tadjibayeva2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Under conditions of unilateral occlusion of the ureter, the development of microhemodynamic disorders ofthe cortical substance of the kidneys was studied both on the damage side and on the contralateral (opposite)side. It has been established that disorders on the side of occlusion depend on the duration of obstructionof the lumen of the ureter, which determines the development of tissue hypoxia and violates trophic renalparenchyma. Dynamically functional disorders of the microvasculature occur at the early (on the 1st, 3rd,and 5th day), and irreversible changes in the renal parenchyma at the later (on the 14th and 30th day) stagesof the experiment. The contralateral one responds to turning off the function of one kidney by adaptiverestructuring of the microhemocirculatory system, which is manifested by dilatation of microvessels and anincrease in the linear velocity of blood flow in them, which ensures its hyperfunction.